PELAKSANAAN PELAYANAN KESEHATAN DASAR GRATIS UNTUK PERSALINAN OLEH BIDAN DESA DI KABUPATEN LAMANDAU PROPINSI KALIMANTAN TENGAH - , Seprit Henry Samosir ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: Local Government of Lamandau District had developed health Insurance program for free basic health services (PKGD) in health centers, subhealth centers, and village maternity clinic. However, midwives had less utilized the program because delivery fee of PKDG was too low. Objective: This study aims to describe the performance of midwife in the village maternity clinic in the implementation of service delivery PKGD programe. Method: The method used was a qualitative method with case study design. Informants were Yankes Head, Section Head of MCH, head of health centers, midwives clinic coordinator, village midwives, and program managers. Data collection was depth interviews, group discussions, and study documents. Analysis of data use theme nalysis. Results: The performance of midwife in childbirth was good, but did not utilize midwives PKDG funds, so that midwives were still asking fees from patients. This is due to the lack of work motivation for using PKDG, incentives and medical services did not in accordance with local conditions, facilities, equipment, and medicines. The expectation of village midwife to work was not achieved because of the lack of regular supervision, monitoring, and evaluation. Conclusion: District Government of Lamandau district needs to create a new local regulation to suit the needs of midwives and the ability to pay of the patients.